2013
DOI: 10.2478/aucft-2013-0010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the New Technology of Cattle Housing Waterbeds on Comfort, Health and Milk Production

Abstract: A new housing technology double-chamber cow waterbeds should provide the animals with greater comfort improve their health and increase milk production. The study was carried out in the stable for dairy cows and heifers. They were stabled in free-stall housing. Rubber mattresses had been replaced with double-chamber cow waterbeds. The aim of the study was to determine their effect on comfort, health, occurrence of mastitis, count of somatic cells, total milk production. The study confirmed the reduction of num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…The smaller pillow is designed for the cow's knees and the larger pillow is for the cow's body. The back edge of the bed is inclined at a 35 ͦ degree angle, which makes a smooth transition from the surface of the water bed to the surrounding space (Simkova et al 2013). According to Geist (2019), dual chamber beds offer additional support for the cow's knees.…”
Section: Water Bedsmentioning
confidence: 99%
See 2 more Smart Citations
“…The smaller pillow is designed for the cow's knees and the larger pillow is for the cow's body. The back edge of the bed is inclined at a 35 ͦ degree angle, which makes a smooth transition from the surface of the water bed to the surrounding space (Simkova et al 2013). According to Geist (2019), dual chamber beds offer additional support for the cow's knees.…”
Section: Water Bedsmentioning
confidence: 99%
“…During the coldest times of the year, waterbeds are preferred because of their ability to retain and store heat. A study by Simkova et al (2013) indicated that cows that preferred water beds were calmer, cleaner, and milk yield increased throughout the entire study period. Dual chamber water beds reduce the incidence of leg diseases, in particular the appearance of hock joints wounds due to pressure (Fulwider et al, 2007).…”
Section: Water Bedsmentioning
confidence: 99%
See 1 more Smart Citation